Принципи на конкуренција и стратегии за реформи во здравствениот систем во Република Македонија - Поповска, Анита (Економски факултет, УКИМ, Скопје, 2013)
The developed world nowadays faces the problem of aging population and fast cost increase in the health sector. In such situation, the governments and other actors responsible for creation of health policies face are challenged by the need to conceptualise and implement reforms in the heath sector. The challenge is twofold: on one hand, the reforms need to be implemented quickly; on the other hand they need to include and address a number of related issues, rather than solving one problem. The latter implies in a need for a comprehensive and inclusive reform framework, based on clearly defined principles. The essential reasons for underlying the importance of the topic are constituted in the need of cost reduction within the healthcare system of Republic of Macedonia to which immense attention shall be paid. For this purpose this thesis presents costs computation model for the entire cycle of patients treatment who suffer from tuberculosis. The computation is made in order to demonstrate the costs for the entire cycle of treatment for patients with tuberculosis and not only for one intervention. This model can serve as a basis, that is, the entire healthcare system shall be extrapolated. Considering the fact that in our country the economic analysis that are widely used worldwide are not known and not used although these analysis contribute to registering of the lacks occurred at fragmentation of the health system in direction of increasing the importance of the patients i.e. the costs covered by the state regarding one medical condition – illness at fragmented health system and doubling the services of insufficient number of patients versus integrated units that follow the direction of improvement of the patients importance.
Competition Principles and Strategies of the Reforms in the Health Care System in Macedonia
Докторска дисертација одбранета во 2013 година на Економскиот факултет во Скопје, под менторство на проф. д–р Владимир Петковски.
Keywords: value-based competition, health system, providers, hospitals, fragmentation, cost